1997
DOI: 10.1161/01.atv.17.11.2589
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HMG-CoA Reductase by Atorvastatin Decreases Both VLDL and LDL Apolipoprotein B Production in Miniature Pigs

Abstract: In the present studies, the 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor atorvastatin was used to test the hypothesis that inhibition of cholesterol biosynthesis in vivo with a consequent reduction in the availability of hepatic cholesterol for lipoprotein synthesis, would (1) reduce very low density lipoprotein (VLDL) apolipoprotein B (apoB) secretion into the plasma, (2) reduce the conversion of VLDL apoB to LDL apoB, and (3) reduce LDL apoB direct synthesis. ApoB kinetic studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
117
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(131 citation statements)
references
References 72 publications
12
117
2
Order By: Relevance
“…We have demonstrated previously in miniature pigs that atorvastatin treatment decreases fasting cholesterol, triglyceride, and VLDL triglyceride concentrations in plasma 36 ; similar responses have been reported in human subjects. [33][34][35] In the present study, decreases were seen in postprandial TRL cholesterol, triglyceride, and RP concentrations.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We have demonstrated previously in miniature pigs that atorvastatin treatment decreases fasting cholesterol, triglyceride, and VLDL triglyceride concentrations in plasma 36 ; similar responses have been reported in human subjects. [33][34][35] In the present study, decreases were seen in postprandial TRL cholesterol, triglyceride, and RP concentrations.…”
Section: Discussionsupporting
confidence: 83%
“…These pigs represent a subset of those reported previously. 36 The 2 protocols were performed 1 week apart.…”
Section: Relationship Between Trl Fractional Clearance Rate (Fcr) Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, VLDL in embryonic circulation contains intact apoB-100 suggesting that apoB-100 is synthesized in the embryo (Hermann et al, 2000). It was reported that inhibition of HMG-CoA reductase by atorvastatin decreases VLDL apoB production in miniature pigs (Burnett et al, 1997). In the present study, in ouo pravastatin injection might inhibit synthesis of apoB-100 and decrease transportation of VLDL to the embryo.…”
Section: Semmentioning
confidence: 46%
“…There is a possibility that hepatic cholesterol content in chick embryos may be altered by in ouo injection of statins since cholesterol is continuously being synthesized in the chick embryo (Shand et al, 1994). In addition, inhibition of hepatic HMG-CoA reductase by atorvastatin reduced both VLDL and apoB production in miniature pigs (Burnett et al, 1997). This decreasein apoB secretion by atorvastatin may, in part, be due to a reduction in apoB mRNA abundance.…”
Section: Introductionmentioning
confidence: 93%